PRAGMATISME SEBAGAI FILSAFAT KONTEMPORER: URGENSI DAN IMPLEMENTASI DALAM ILMU KEISLAMAN - Roisah Fathiyatur Rohmah (Fakultas Ushuluddin, Adab dan Dakwah, Universitas Islam Negeri (UIN) Datokarama Palu, Indonesia, 2024)
This research discusses the urgency of the philosophy of pragmatism for the advancement of Islamic science and its implementation. The philosophy of Pragmatism was coined by Charles Sanders Peirce who explained the concept of thinking (methodology). The components of pragmatism philosophy are belief, the habit of mind, doubt, inquiry, and meaning. So, to give birth to renewal in Islamic knowledge, doubt is needed regarding beliefs that have become habits of mind. Once there is doubt, you can carry out an inquiry through scientific research. Meaning can be seen from whether the research is useful or not. This type of research is library research with the sourcebook Contemporary Analytic Philosophy published by Macmillan Publishing New York in 1981 by Milton K. Munitz. The way this research works is to apply the concept of pragmatism philosophy to the thinking of Muslim scholars, namely Jasser Auda regarding maqashid al-syari'ah and Abdullah Saeed regarding contextual interpretation. This research shows that the two figures started from a doubt (doubt) in the methodological construction of classical jurisprudence and the interpretation of the Al-Qur'an which is based on existing beliefs. The two figures carried out an inquiry to produce new ideas for the advancement of Islamic knowledge.